Characteristics of giant piezoelectricity around the rhombohedral-tetragonal phase boundary in (K, Na)NbO3-based ceramics with different additives. Issue 31 (21st August 2015) - Wang, Xiaopeng; Zheng, Ting; Wu, Jiagang; Xiao, Dingquan; Zhu, Jianguo; Wang, Hui; Wang, Xiangjian; Lou, Xiaojie; Gu, Yueliang
<x xml:space="preserve">Abstract</x> We confirmed the EPT in KNN-based ceramics through experiment and theory, and found it could play a positive role in the piezoelectricity.